Pengembangan Media Pembelajaran Berbasis Multimedia Menggunakan Macromedia Flash dalam Fiqih Islam Materi Pokok Sholat dan Zakat - Said Nur Alim (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2021)
The development of science and technology increasingly encourages reform efforts in the use of technological results in the learning process. Teachers are required to be able to use these tools in accordance with the developments and demands of the times. And it is a must for teachers to be able to master technology in order to achieve the expected learning objectives, the problems in this study are: (1) how to develop multimedia-based learning media using Macromedia Flash in Fiqh learning the subject matter of Prayer and Zakat? (2) how is the effectiveness of multimedia-based learning media using Macromedia Flash in Fiqh learning the subject matter of Prayer and Zakat? The development was carried out using the Research and Development (R&D) method with several stages, namely: analyzing potential and papers, gathering information, product design, design validation, design revision, product testing, product revision, product usage trials. The results of the design validation stages, product trials and usage trials are used to improve the developed products for maximum results. Based on the trials that have been carried out, the results are as follows: a) pre-test and post-test with an initial average of 54.57 and an increase after learning with a final score of 86.85, thus the post-test average of 32.28 can be categorized in good criteria. b) Based on the practical analysis conducted in the field, some teachers and students gave a positive response to the developed product. The effectiveness of learning using Macromedia Flash, The increase in the average value of pre-test and post-test that has been carried out by respondents from one lesson, there is an increase of 32,285714286 from 54,571428571 to 86.857142857, There is a positive response of students to the development of media using Macromedia flash i.e. 79% of students categorize very well, 13% of students categorize good and 8% of students categorize enough.